If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + -1(7 + -6n) = 13 4n + (7 * -1 + -6n * -1) = 13 4n + (-7 + 6n) = 13 Reorder the terms: -7 + 4n + 6n = 13 Combine like terms: 4n + 6n = 10n -7 + 10n = 13 Solving -7 + 10n = 13 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 10n = 13 + 7 Combine like terms: -7 + 7 = 0 0 + 10n = 13 + 7 10n = 13 + 7 Combine like terms: 13 + 7 = 20 10n = 20 Divide each side by '10'. n = 2 Simplifying n = 2
| 6x+3=3(2x+3) | | 2x-11=23 | | 3x=52 | | (9x-8y-11)-(5x-9y+1)= | | -8=1.3x+x | | 10=-2.3(4x+5) | | 18b-21=15b+3 | | 7x-[-5]=-9 | | 4=2.3x+9-1.3x | | 6m=2m-8 | | 2x(28)=x+4 | | 26x+24=-39x-6 | | -6x-9x+11= | | 3.4(x+2)=-1 | | 2x-28=x+4 | | 3n-4=10 | | (6x-9y-4)-(7x-12y-6)= | | 2(4x+-3)+-8=4+2x | | 7.4gr*1200fps= | | 4x^2+21y^2=13 | | 8m=96-16 | | 9-5x=12-(3x-5) | | 6w+6=37 | | 12p=6-3 | | 4*2x-5=6 | | 11x-5=7x+7 | | x/8+6= | | 9=1+m/3 | | (x^2+15)(x^2+3)=0 | | 4(x-3)=-2x+18 | | x+7-15= | | -6*3x+15=18 |